Bringing critical realism to nursing practice: Roy Bhaskar's contribution - Williams, Lynne (Nursing philosophy, 2017)
In the context of modern nursing practice that is embedded within complex social situations, critical discussions about the contribution of major philosophers are relevant and important. Whilst nurse theorists have advanced and shaped nursing as a discipline, other major philosophers can offer much to advance nursing enquiry. In this paper, we focus on philosopher Roy Bhaskar who, amongst others, developed critical realism, a philosophy for social science which connects with how many of us think about the world. Bhaskar's work focuses our attention on the interplay between structure and agency and on the search for the causative or generative mechanisms that explain the social world. Bhaskar was interested in human emancipation, and we suggest his work is of great importance to advance understanding of complex social situations. Critical realism has already been endorsed by a range of disciplines, especially in research which focuses on real problems and acknowledges the complexities of the social world. In recent evidence from healthcare literature, there has been a surge in research using realist methodology (realist evaluation and realist synthesis), which is underpinned by the philosophy of critical realism and which offers a different perspective to understanding nursing and healthcare problems through the realist lens. However, we suggest that sufficient attention is not always paid to the philosophical roots of this methodology. In this paper, we provide insight into Bhaskar's work and demonstrate how research positioned within critical realism and realist methodology can advance nursing and healthcare-related knowledge. Through shining a light on Bhaskar, we illustrate how critical realism philosophy is a natural fit with human and health science enquiry, including nursing.